2015
DOI: 10.1038/pcan.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

A review of rectal toxicity following permanent low dose-rate prostate brachytherapy and the potential value of biodegradable rectal spacers

Abstract: Permanent radioactive seed implantation provides highly effective treatment for prostate cancer that typically includes multidisciplinary collaboration between urologists and radiation oncologists. Low dose-rate (LDR) prostate brachytherapy offers excellent tumor control rates and has equivalent rates of rectal toxicity when compared with external beam radiotherapy. Owing to its proximity to the anterior rectal wall, a small portion of the rectum is often exposed to high doses of ionizing radiation from this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…The implanted rectum spacer remains in place over the course of the RT treatment, and the spacer biodegrades naturally within 6 months after implantation [ 44 ]. Different types of rectum spacers have been developed: an absorbable hydrogel, a hyaluronic acid, a collagen, and a saline-filled balloon [ 44 46 ]. Several studies are available on the dosimetry, acute outcome, and cost-effectiveness of a rectum spacer; however, no long-term results are available yet [ 47 56 ].…”
Section: Preventionmentioning
confidence: 99%
“…The implanted rectum spacer remains in place over the course of the RT treatment, and the spacer biodegrades naturally within 6 months after implantation [ 44 ]. Different types of rectum spacers have been developed: an absorbable hydrogel, a hyaluronic acid, a collagen, and a saline-filled balloon [ 44 46 ]. Several studies are available on the dosimetry, acute outcome, and cost-effectiveness of a rectum spacer; however, no long-term results are available yet [ 47 56 ].…”
Section: Preventionmentioning
confidence: 99%
“…However, we previously reported that the absolute differences in baseline scores between men enrolled in the CEASAR study who completed the baseline survey before versus after starting treatment were very small (range, 1‐3 points), and the Prostate Cancer Outcome Study validation study demonstrated most men accurately recall prediagnostic function 6 months after prostate cancer diagnosis 36,37 . Finally, this study did not account for the use of biodegradable rectal spacers, preoperative magnetic resonance imaging, or other technical advancements for LDR boost 38,39 . As such, the addition of biodegradable rectal spacers may lead to decreases in bowel toxicity, and preoperative magnetic resonance image planning allows better urethral delineation, which may translate to improved urinary toxicity.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, no guidelines exist for the use of spacers in radiotherapy. Reports in the literature describe the use of these techniques to minimize normal tissue dose in head and neck, cervical, and prostate cancer [6-8]. While short-term follow-up shows favorable safety profiles, long-term data is not presently available to evaluate the delayed complications of prophylactic spacer use in brachytherapy.…”
Section: Introductionmentioning
confidence: 99%